The Causal Effects of Adolescent School Bullying Victimisation on Later Life Outcomes - Emma Gorman; Colm P. Harmon; Silvia Mendolia; Anita Staneva; Ian Walker (Institute of Labor Economics (IZA), 2019)
We use rich data on a cohort of English adolescents to analyse the long-term effects of experiencing bullying victimisation in junior high school. The data contain self-reports of five types of bullying and their frequency, for three waves of the data, when the pupils were aged 13 to 16 years. Using a variety of estimation strategies - least squares, matching, inverse probability weighting, and instrumental variables - we assess the effects of bullying victimisation on short- and long-term outcomes, including educational achievements, earnings, and mental ill-health at age 25 years. We handle potential measurement error in the child self-reports of bullying type and frequency by instrumenting with corresponding parental cross-reports. Using a detailed longitudinal survey linked to administrative data, we control for many of the determinants of bullying victimisation and child outcomes identified in previous literature, paired with comprehensive sensitivity analyses to assess the potential role of unobserved variables. The pattern of results strongly suggests that there are important long run effects on victims - stronger than correlation analysis would otherwise suggest. In particular, we find that both type of bullying and its intensity matters for long run outcomes.
Keywords: I21; I24; I26; J24; 330; bullying; victimization; long term outcomes